raming and Narrativizing of Borders around the post- Habsburg Rijeka: Giovanni Comisso’s Il porto dell’amore and Viktor Car Emins Danuncijada - Bobinac, Marijan (Poznańskie Studia Slawistyczne, 2025)
Between 1917 and 1923, as European continental empires were shattering after the lost world war and new nation-states were created on their ruins, several radical political-ideological movements emerged as well, employing various types of (para)military violence to achieve their goals. In the post-imperial context, (para)military violence was particularly employed in numerous conflicts over new boundary demarcations in the areas known as shatter zones (Bartov, Weitz, 2013) in former multi-ethnic empires, areas for which national activists had been disputing for decades. D’Annunzio’s occupation of Rijeka in 1919/1920 is considered one of the most significant examples of postimperial border conflicts. In this paper, two literary stagings of the border dispute around Habsburg Rijeka will be presented: Giovanni Comisso’s Il porto dell’amore and Viktor Car Emin’s Danuncijada, two very different, but thematically closely related reflections on D’Annunzio’s Fiume exploit.